2012
DOI: 10.1186/1476-069x-11-s1-s3
|View full text |Cite
|
Sign up to set email alerts
|

We’re only in it for the knowledge? A problem solving turn in environment and health expert elicitation

Abstract: BackgroundThe FP6 EU HENVINET project aimed at synthesizing the scientific information available on a number of topics of high relevance to policy makers in environment and health. The goal of the current paper is to reflect on the methodology that was used in the project, in view of exploring the usefulness of this and similar methodologies to the policy process. The topics investigated included health impacts of the brominated flame retardants decabrominated diphenylether (decaBDE) and hexabromocyclododecane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…It is worth noting that nervous system damage in infants is likely to be permanent when it occurs during the perinatal period, a crucial window of development ( Rice and Barone, 2000 ). Moreover, many epidemiological studies have confirmed that DEHP exposure is positively associated with the pathogenesis of neurodevelopmental disorders, such as autism spectrum disorder and attention deficit hyperactivity disorder symptoms ( Benson, 2009 ; Pan et al, 2011 ; Keune et al, 2012 ; Upson et al, 2013 ; Chopra et al, 2014 ; Kim et al, 2015 ; Park et al, 2015 ; Philippat et al, 2015 ). Therefore, the negative effects of perinatal exposure to DEHP on the neurodevelopment of offspring have aroused widespread concern ( Pan et al, 2011 ; Philippat et al, 2015 ; Zarean et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that nervous system damage in infants is likely to be permanent when it occurs during the perinatal period, a crucial window of development ( Rice and Barone, 2000 ). Moreover, many epidemiological studies have confirmed that DEHP exposure is positively associated with the pathogenesis of neurodevelopmental disorders, such as autism spectrum disorder and attention deficit hyperactivity disorder symptoms ( Benson, 2009 ; Pan et al, 2011 ; Keune et al, 2012 ; Upson et al, 2013 ; Chopra et al, 2014 ; Kim et al, 2015 ; Park et al, 2015 ; Philippat et al, 2015 ). Therefore, the negative effects of perinatal exposure to DEHP on the neurodevelopment of offspring have aroused widespread concern ( Pan et al, 2011 ; Philippat et al, 2015 ; Zarean et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The causal diagram approach has proven to be a suitable conceptualization, simplification and visualization technique that allows communication linking the scientific disciplines involved, as documented by a wide range of examples [1,2,81,82]. In the near future it is envisaged to use this diagram as the basis for an internet-based tool for knowledge assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the consensus or the lack of it needs to lead to appropriate actions. These needs are addressed by an expert elicitation methodology described by Keune et al [ 19 ], applied in the case studies [ 10 - 16 ].…”
Section: Approach and Challengesmentioning
confidence: 99%